Flaubert et la stéréographie française, 1850-1880 - Arden Reed (Flaubert: Revue Critique et Génétique)
Flaubert was a strikingly visual writer, who needed « to see » what he evoked in words. Like a time capsule, French stereography from 1850 to 1880 captures for us his visual surroundings and his cultural context: a world of visual clichés that parallel his idées reçues: romantic plots, exotic locations, erotic fantasies, people represented like objects and the reverse. Even for Flaubert—who « detests photographs », these stereographs « illlustrate » his texts.